Re-designing industrial products on a multi-objective basis: a case study - Achillas, C; Aidonis, D; Vlachokostas, C; Folinas, D; Moussiopoulos, N (The Journal of the Operational Research Society, 2013)
Environmentally conscious product design has received significant attention recently. Apart from new products' development, environmental considerations may also apply for products that manufacturers have already launched in the market. In this case, manufacturers can also make use of their considerable experience gained over the phases following product design (eg production, use, end-of-life, etc) in order to promote substantial improvements as regards their re-designed products' performance. This paper presents a methodological framework for manufacturers based on Multiple Objective Integer Programming in order to re-design industrial products. The proposed approach includes re-designed product's cost, environmental impact, weight and ease of disassembly. The methodology is applied to a real-world case study, that of netMod network terminal.